Corporate Social Responsibility in the European Union: An Assessment of CSR Strategy - (:unkn) unknown (SPRINGER INTERNATIONAL PUBLISHING AG, 2015)
This article investigates the role of Corporate Social Responsibility (CSR) in corporate governance. In the context of CSR's function in corporate governance, this study specifically focuses on the Europe 2020: European Union's Growth Strategy, and its corresponding directives related to CSR. Not only are the Member States of the EU requested to comply with the regulations, and laws, but the candidate countries are also expected to improve their sustainability performances as well as their national frameworks to foster social responsibility (European Commission, Europe 2020 - EU - wide headline targets for economic growth. Europe 2020. http://ec.europa.eu/europe2020/europe-2020-in-a-nutshell/targets/index_en.htm, Accessed 15 Mar 2014, 2011). The study investigates the European Union's 2020 Growth Strategy with a driven focus towards CSR targets to provide a comprehensive framework of what the EU has accomplished. In doing so, this paper seeks to depict a picture based on a real industry: the mining industry and the details of 2014 Soma Disaster in the Coal Mining industry in Turkey. With an attempt to demonstrate how CSR may be improved in terms of environmental as well as corporate governance at the EU level, a strategic assessment is provided. The authors present case study evidence from the Mining industry and the Soma mining disaster which occurred in 2014 in Turkey that shows that established and newly formed governmental regulations and reforms relating to health and safety of the workers in the mining industry and the conditions of the mining shafts can be instrumental in implementing humane, civilized, ethical and acceptable norms in the form of corporate governance. These reforms potentially lead to collaborative cooperation of the companies with the governments and form corporate governance, part of a sustainable, ethical, and socially responsible conduct that facilitates implications of safety measures culminated by a health, and safe labour conditions in a given country in the context of the industry. The study incorporates contemporary literature and documents of the European Union's Growth Strategy, which portray the expectations and directives of the body as to the CSR practices of the member and candidate countries, emanating from the Europe 2020 configuration. In doing so, it takes a process approach and provides much needed qualitative evidence in CSR research via a case from the mining industry.